Project Management in Innovation Networks - Melski, Adam; Borchert, Jan Eric; Hagenhoff, Svenja (2008)
In times of market globalization, aggravated competition and the shortening of product life cycles, many companies have turned to innovations as elixirs for their continued existence (Little, 1997). Companies cope with increased innovation requirements by increasing their specialization in a certain field. This makes new innovation ideas more probable; however, it also complicates the process from conception to realization. Traditional leadership systems with rigid hierarchical structures are increasingly replaced by more flexible, interdisciplinary work forms, with networks becoming the prevailing form of organization (Man, 2004). Innovation plans are usually carried out in projects, thus the management of innovation projects has become the center of attention. However, the failure of many innovation projects sheds doubt on the usefulness of project management (PM). Studies demand robust process controlling to replace the more delicate PM (Hauschildt 2003). This article examines to what extend PM may be used as a “universal management instrument” (Seibert, 1998, p. 25) in innovation networks. In addition, further concepts and instruments that should be added to PM in innovation networks will be introduce